Designing of a dual-band printed reflectarray based on the modified Floque cell - S. V. Ballandovich (Известия высших учебных заведений России: Радиоэлектроника, 2015)
Method of designing of a dual-band printed reflectarray with improved characteristics is described. Calculated data for printed reflectarrays based on the modified and common Floque cell are presented.